Single ring dual-band bandpass filter with meander for WLAN application / Mohd Musalman Abdullah Sani - Abdullah Sani, Mohd Musalman (2014)
A single ring resonator dual-band bandpass filter using quarter-wavelength resonators suitable for WLAN applications is presented in this paper. Both side of ring resonator consist of quarter-wavelength parallel coupled lines. In further reducing the size of the filter, meander structure is applied to an existing design. Using different number of meander slots, a microstrip dual-band single ring resonator are applied and realized on FR4 substrate to suite filter operating at 2.5GHz and 5.2GHz. Simulation is carried out in analyzing the performance of the design using Advance Design System (ADS) and fabrication is done to validate the topology.